mKRISHIÂ®- Fisheries: A Public Private Partnership innovation toward business commercialization - Singh, Dineshkumar (Indian Farming, 2015)
The Central Marine Fisheries Research Institute, Mumbai Centreof ICAR with TCS Innovation Lab has developed an informationsservice for the benefit of fisherman useing the mKRISHI platform.This service is beneficial for fishermen in many ways, for e.g. itindicates the potential fishing zones with the shoals of pelagic fishes. The wind speed and direction helps in also spotting the probable danger zones. The early warning oceanic wind speed and direction advisories help the fishermen to avoid those areas or move towards some safer places in the sea.